Аналіз електронних фільтрів Баттерворта чисельними методами - Северин, Валерій Петрович; Нікуліна, Олена Миколаївна; Буряковський, В. С. (НТУ "ХПІ", 2014)
Створено математичні моделі електронних фільтрів Баттерворта різних порядків. На основі матричних методів інтегрування систем диференціальних рівнянь розроблені алгоритми та програми для обчислення перехідних процесів в фільтрах та їх прямих показників якості. Розраховані амплітудно-частотні характеристики, перехідні процеси та прямі показники якості фільтрів Баттерворта різних порядків.

On the base of the placement of the poles of transfer functions for Butterworth's filters of different orders the mathematical models are created. The transfer functions of Butterworth filters odd and even orders are presented. The mathematical model of Butterworth filter arbitrary order as a linear system of differential equations is developed. For integration of linear systems of differential equations the method with using formula of definition of matrix exponential and its integral is considered. Algorithms for calculation of transients in filters and their quality indexes are designed. Amplitude-frequency characteristics, transient functions and direct quality indexes of Butterworth filters of different orders are calculated. Graphics of amplitude-frequency characteristics and transients of filters are built. The values of direct quality indexes of Butterworth filters of different orders are submitted. With increasing order of Butterworth filter all its direct quality indexes significantly increasing, which make it necessary to solve optimization problems of filters.
Analysis of the electronic filters Butterworth by numerical methods
Keywords: фільтр Баттерворта; електронні фільтри; математична модель; передавальна функція; перехідні процеси; показники якості; electronic filters; Butterworth filter; mathematical model; transfer function; transients; direct quality indexes